PELATIHAN PENGELOLAAN SUMBER DAYA MANUSIA DALAM RANGKA PENINGKATAN WIRAUSAHA DI DELITUA - Chon Cho Reynols; Merry Moy Mita; Supriadi Siagian (Jurnal Pemberdayaan Masyarakat, 2026)
The development of Micro, Small and Medium Enterprises (MSMEs) in Delitua District faces latent challenges in the form of limited Human Resources (HR) management capacity. Most local entrepreneurs still rely on conventional management without planning, division of labor and structured work motivation. This Community Service (PkM) activity aims to provide practical understanding and skills for entrepreneurs in Delitua in managing human resources to increase productivity and business competitiveness. The method used in this service is carrying out intensive training which includes delivering material, interactive case studies, as well as mentoring sessions in creating simple SOPs (Standard Operating Procedures). The service partners consist of 25 MSME actors in the Delitua area. Evaluation of the success of activities is carried out by distributing pre-test and post-test questionnaires. The results of the service showed an 85% increase in participants' understanding regarding the importance of HR governance, which includes aspects of simple recruitment, division of tasks (job descriptions), and providing non-financial incentives to increase employee loyalty. Through this training, entrepreneurs in Delitua are now able to implement more organized HR management for more profitable business sustainability.